Detection of the faulted network element usingfrequency spectrum features of zero-sequence currentunder transient earth faults in the network with neutralgrounding through Peterson-coil; Electrical, Electronics, Computer Engineering and their Applications (EECEA2016) - Moldovanova E. A. Evgeniya Aleksandrovna (2016, 2016)
Title screen